High dimensional microarray data classification using correlation based feature selection - Abid, Hassan; Md. Akhtaruzzaman, Adnan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/